Dyspnea is associated with poor physical performance among community-dwelling older adults: a population- based cross-sectional study - Silva, Caroline de Fátima Ribeiro; Pegorari, Maycon Sousa; Matos, Areolino Pena; Ohara, Daniela Gonçalves (São Paulo Medical Journal, 2020)
BACKGROUND: Dyspnea and poorer physical performance are conditions that may be related and be present among the elderly. However, few studies have evaluated associations between these variables. OBJECTIVE: To determine whether there is an association between dyspnea and physical performance among community-dwelling older adults of both sexes (age 60 years and over). DESIGN AND SETTING: Cross-sectional study conducted in the city of Macapá, state of Amapá, Brazil. METHODS: Socioeconomic and health data were collected using a structured form. Frailty syndrome was assessed based on the frailty phenotype proposed by Fried et al. Dyspnea was measured using the modified Medical Research Council (mMRC) scale and physical performance was measured using the Short Physical Performance Battery (SPPB). Data were analyzed using a linear regression model. RESULTS: A total of 411 subjects (70.15 ± 7.25 years) were evaluated, most of them females (66.4%). It was observed from the mMRC scale that 30.9% (n = 127) of the subjects had some dyspnea symptoms: grade 1 was most frequent. The physical performance score from the SPPB was 9.22 ± 2.01. Higher dyspnea scores were associated with poor physical performance, both in the crude analysis (β = -0.233; P = 0.028) and after adjustment for frailty condition (β = -0.148; P = 0.002) and for the socioeconomic and health variables (age, sex, number of diseases, smoking habit and frailty status) (β = -0.111; P = 0.025). CONCLUSION: Higher dyspnea score was independently associated with poor physical performance among community-dwelling older adults.